2014
DOI: 10.1682/jrrd.2013.05.0103
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study: Computer-based virtual anatomical interactivity for rehabilitation of individuals with chronic acquired brain injury

Abstract: Abstract-Deficiencies in upper-limb motor function and executive functioning can compromise an affected individual's ability to complete everyday activities. Impaired motor and executive functioning therefore pose a risk to increasing numbers of veterans who have been diagnosed with acquired brain injury. This article reports on changes in upper-limb motor function and executive functioning of 12 adult participants with chronic acquired brain injury using a novel, computer-based, motor and cognitive rehabilita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…One comparative study was a cross-over study 17 . Two non-comparative studies evaluated all acquired brain injury patients, meaning that patients that had previously suffered a stroke were also included: one study had one patient with TBI and three stroke patients 18 , and another study had four patients with TBI and eight stroke patients 19 .…”
Section: Study Characteristicsmentioning
confidence: 99%
“…One comparative study was a cross-over study 17 . Two non-comparative studies evaluated all acquired brain injury patients, meaning that patients that had previously suffered a stroke were also included: one study had one patient with TBI and three stroke patients 18 , and another study had four patients with TBI and eight stroke patients 19 .…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Of the studies identified, two evaluated the CogMed QM software; 9,13 two studies evaluated study-specific computer-based cognitive training software; 11,14 and two studies evaluated Parrott software. 15,16 Of the remaining, one study evaluated Rehacom; 12 one study evaluated ProMotor Exercise Games; 17 one study evaluated a virtual reality cognitive rehabilitation program; 18 and one study used both Attention Process Training (APT-3) and Lumosity games. 19 Two studies randomized participants to receive rehabilitation plus the intervention or rehabilitation alone.…”
Section: Discussionmentioning
confidence: 99%
“…Simmons et al 17 tested a computer-based virtual reality intervention among participants with acquired brain injury recruited from an adult care center on upper extremity motor function and executive function. The intervention study was conducted using a three-level repeated measures design.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations